Institutional Financial Sustainability through Innovative Financing Management: Evidence from Madrasah Aliyah - Riinawati; Syaiful Bahri; Rusnadi; Nadzmi Akbar; Bambang Sigit Widodo; Iqbal Asyauqi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study is motivated by the increasing need for effective and sustainable financial management in educational institutions, particularly in madrasahs facing dynamic financial challenges. The study aims to analyze financing management innovations in supporting financial efficiency and sustainability at Madrasah Aliyah Siti Mariam Banjarmasin. A descriptive qualitative approach was employed, with data collected through semi-structured interviews, direct observation, and documentation of madrasah financial statements. The data were analyzed thematically to identify effective financial management practices and to explore the supporting and inhibiting factors in implementing technology-based financial innovations. The findings reveal that the madrasah has implemented structured budget planning through the Revenue and Expenditure Budget Plan (RAPB), along with systematic financial recording and the use of financial applications that enhance transparency and accountability. The main sources of funding include tuition fees, internal business units, and contributions from students’ guardians, supported by ongoing efforts to diversify funding sources for long-term sustainability. However, challenges remain in optimizing technology use and improving human resource capacity in financial management. The study implies that strengthening technology-based financial systems and enhancing human resource competencies are essential for improving financial efficiency and ensuring institutional sustainability. These findings provide practical insights for madrasah administrators and policymakers in developing more transparent, accountable, and innovative financing management strategies.